Supported Liquid Membrane Separation of Chromium(VI) from Effluents - Parakudyil, Ancy S.; Michael, K.M.; Pillai, Ajai K. (Journal of Membrane and Separation Technology, 2013)
Supported liquid membrane (SLM) technique was used for the selective separation of Chromium(VI) from iron ore leachates. It was carried out using membrane made of Teflon loaded with Aliquat -336 in n-dodecane. This method is applicable for the removal of chromium(VI) from industrial effluents, and synthetic wastewater. The effect of feed phase, carrier concentration and stripping agent concentrations were studied and optimized. At pH 5.5 SLM transport cell would efficiently separate Chromium(VI) from feed phase to stripping phase.